Methodologies and Emerging Technologies for the Evaluation of the Hematopoietic System. (October 2022) - Poitout-Belissent, Florence; Vitsky, Allison; Smith, Mark A.; Sirivelu, Madhu P.
Hematology and bone marrow analysis is central to our understanding of the hematopoietic system and how it responds to insults, and this session presented during the 2022 STP symposium provided a review of current and novel approaches for the evaluation of the hematopoietic system in the context of nonclinical investigations. This publication summarizes the information presented on novel approaches for evaluation of the hematopoietic system using automated hematology analyzers, including details around the quantitative assessment of bone marrow cell suspensions as well as introducing several newly available hematology parameters. It was followed by a discussion on intravital microscopy and live cell imaging and how these methods can assist with de-risking hematopoiesis-associated safety concerns, and a review of recent assays using artificial intelligence for the evaluation of bone marrow.